Inhibition of tissue factor:factor VIIa–catalyzed factor IX and factor X activation by TFPI and TFPI constructs. (12th October 2014) - Peraramelli, S.; Thomassen, S.; Heinzmann, A.; Rosing, J.; Hackeng, T. M.; Hartmann, R.; Scheiflinger, F.; Dockal, M.
Summary Background TFPI is a Kunitz‐type protease inhibitor that downregulates the extrinsic coagulation pathway by inhibiting factor Xa (FXa) and FVIIa. All three Kunitz domains (KD1, KD2, and KD3) and protein S are required for optimal inhibition of FXa and FVIIa. There is limited information on Kunitz domain requirements of the inhibition of TF:FVIIa–catalyzed FIX and FX activation by TFPI. Aim To investigate the role of the Kunitz domains of TFPI and protein S in the inhibition of FX and FIX activation. Methods Inhibition of TF:FVIIa–catalyzed FX and FIX activation by full‐length TFPI (TFPIFL) and TFPI constructs was quantified from progress curves of FXa and FIXa generation measured with chromogenic substrates. Results and conclusions TFPIFL inhibited TF:FVIIa–catalyzed FIX activation with a Ki of 16.7 nmol L–1. Protein S reduced the Ki to 1.0 nmol L–1. TFPI1‐150 and KD1‐KD2 had 10‐fold higher Ki values and were not stimulated by protein S. Single Kunitz domains were poor inhibitors of TF:FVIIa‐catalyzed FIX activation (Ki >800 nm). FX activation was measured at limiting FVIIa and excess TF or vice versa. At both conditions, TFPIFL, TFPI1‐150, and KD1‐KD2 showed similar inhibition of FX activation. However, at low phospholipid concentrations, TFPIFL was ~ 15‐fold more active than TFPI1‐150 or KD1‐KD2. Apparently, excess phospholipids act as a kind of sink for TFPIFL, limiting its availability for TF:FVIIa inhibition. Preformed FXa:TFPIFL/1‐150 complexes rapidly and stoichiometrically inhibited FIX and FX activation by TF:FVIIa, indicating that binary TFPI:FXa complex formation is the limiting step in TF:FVIIa inhibition. Protein S also enhanced inhibition of TF:FVIIa–catalyzed FX activation by TFPI.